Pengaruh Motivasi Terhadap Minat Menjadi Guru Pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Muhammadiyah Bengkulu - Meirani Meirani; Winda Qoirunnada (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the motivation to become a teacher, interest in being a teacher and the influence of motivation on interest in becoming a teacher in Economic Education students, FKIP University of Muhammadiyah Bengkulu. This type of research is quantitative research. The research population is students of Economics Education FKIP University of Muhammadiyah Bengkulu batch 2018, 2019, 2020. The sampling technique uses proportional stratified random sampling. Data collection techniques are observation, questionnaires, and documentation. Simple linear regression data analysis technique. The results showed that: Motivation to become a teacher with a total of 31 respondents who answered the questionnaire was very high 3 respondents with a percentage of 10%, high 13 respondents with a percentage of 42%, low 15 respondents with a percentage of 48%, and very low none, for interest in becoming a teacher with a total of 31 respondents who answered the questionnaire very high 6 respondents with a percentage of 19%, high 9 respondents with a percentage of 29%, low 16 respondents with a percentage of 52%, and very low none. There is an influence of motivation on the interest in becoming a teacher in Economics Education FKIP students, University of Muhammadiyah Bengkulu. It is obtained from F arithmetic > F table (5.37 > 4.18) and the level of influence is 23%.